Synergistic antibacterial effects of ultrasound combined nanoparticles encapsulated with cellulase and levofloxacin on Bacillus Calmette-Guérin biofilms - Zhang, Zhifei; Zhang, Yuqing; Yang, Min; Hu, Can; Liao, Hongjian; Li, Dairong; Du, Yonghong (Frontiers in Microbiology, 2023)
Tuberculosis is a chronic infectious disease, the treatment of which is challenging due to the formation of cellulose-containing biofilms by Mycobacterium tuberculosis (MTB). Herein, a composite nanoparticle loaded with cellulase (CL) and levofloxacin (LEV) (CL@LEV-NPs) was fabricated and then combined with ultrasound (US) irradiation to promote chemotherapy and sonodynamic antimicrobial effects on Bacillus Calmette-Guérin bacteria (BCG, a mode of MTB) biofilms. The CL@LEV-NPs containing polylactic acid-glycolic acid (PLGA) as the shell and CL and LEV as the core were encapsulated via double ultrasonic emulsification. The synthesized CL@LEV-NPs were uniformly round with an average diameter of 196.2 ± 2.89 nm, and the zeta potential of −14.96 ± 5.35 mV, displaying high biosafety and sonodynamic properties. Then, BCG biofilms were treated with ultrasound and CL@LEV-NPs separately or synergistically in vivo and in vitro. We found that ultrasound significantly promoted biofilms permeability and activated CL@LEV-NPs to generate large amounts of reactive oxygen species (ROS) in biofilms. The combined treatment of CL@LEV-NPs and US exhibited excellent anti-biofilm effects, as shown by significant reduction of biofilm biomass value and viability, destruction of biofilm architecture in vitro, elimination of biofilms from subcutaneous implant, and remission of local inflammation in vivo. Our study suggested that US combined with composite drug-loaded nanoparticles would be a novel non-invasive, safe, and effective treatment modality for the elimination of biofilm-associated infections caused by MTB.